Identification of soft competencies aspects in human resource development in the industrial era 4.0 - Tarigan, Medianta; Fadillah, Fadillah (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
This systematic literature review aims to provide an overview of the research related to the soft competency aspects required in industry 4.0 on human capital development. This study used the PRISMA model and included 284 articles from the Scopus, ScienceDirect, and Springerlink databases and three additional report articles with a publication period of 2010 to 2021, which were then selected according to inclusion and exclusion criteria. Thirty-two articles are considered eligible for the further qualitative analysis process. All were analyzed using a content analysis approach that three experts carried out. The result of the analysis shows that articles mention 11 aspects of soft competencies. These aspects are leadership, working with people, customer orientation, communication, task & responsibility engagement, decision making, problem-solving, creative & innovative orientation, flexibility & adaptability, learning orientation, emotional resilience, and problem-solving. These eleven aspects are then classified into Managing People, Tasks, and Self Competencies.